Atmosphere, clouds, and climate - Randall, David A. (David Allan), 1948- (Princeton primers in climate., 2012)
The atmosphere is critical to climate change. It can amplify shifts in the climate system, and also mitigate them. This primer offers an introduction to these atmospheric processes and how they work, written by a leading expert on the subject. In an overview of key atmospheric processes, the author looks at how our climate system receives energy from the sun and sheds it by emitting infrared radiation back into space. The atmosphere regulates these radiative energy flows and transports energy through weather systems such as thunderstorms, monsoons, hurricanes, and winter storms. He explains how these processes work, and also how precipitation, cloud formation, and other phase changes of water strongly influence weather and climate. He discusses how atmospheric feedbacks affect climate change, how the large-scale atmospheric circulation works, how predicting the weather and the climate are fundamentally different challenges, and much more. This primer is an introduction to atmospheric processes and the vital role they play in our climate system.